Carboidratos ácido-digeríveis medidas físicas de sete feijões (Phaseolus vulgaris L.) consumidos em Viçosa, Minas Gerais - Franco Feitosa Teles, Francisco; Martins Batista, Cid; Paiva del Giúdice, Maria de Lourdes; Fernandes Santana, Bernadete; Lelis Leal, Targina (Revista Ceres, 2025)
Seven types of beans (Phaseolus vulgaris L.), grown in the state of Minas Gerais, Brazil, were analysed for acid-digestible carbohydrates (ADC).